2008
DOI: 10.1289/ehp.10790
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Reproductive Development in Sons of Women Occupationally Exposed to Pesticides during Pregnancy

Abstract: ObjectivesThe aim of this prospective study was to investigate whether occupational pesticide exposure during pregnancy causes adverse effects on the reproductive development in the male infants.Design and measurementsPregnant women employed in greenhouses in Denmark were consecutively recruited, and 113 mother–son pairs were included. The mothers were categorized as occupationally exposed (91 sons) or unexposed (22 sons) to pesticides during pregnancy. Testicular position and volume, penile length, and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(84 citation statements)
references
References 58 publications
(88 reference statements)
3
80
0
1
Order By: Relevance
“…Females involved in agricultural work reported a higher percentage of adverse outcomes of pregnancy (abortion, stillbirth and congenital anomalies) compared to females not engaged in agriculture, which agrees with other studies [22][23][24][25][26]. The intricate processes of the menstrual cycle, ovum production, fertilization, implantation, growth and development of the foetus may be particularly susceptible to low-dose exposures to endocrine disruptors.…”
Section: Helping In Farming Operationssupporting
confidence: 87%
“…Females involved in agricultural work reported a higher percentage of adverse outcomes of pregnancy (abortion, stillbirth and congenital anomalies) compared to females not engaged in agriculture, which agrees with other studies [22][23][24][25][26]. The intricate processes of the menstrual cycle, ovum production, fertilization, implantation, growth and development of the foetus may be particularly susceptible to low-dose exposures to endocrine disruptors.…”
Section: Helping In Farming Operationssupporting
confidence: 87%
“…Female Danish greenhouse workers exposed to current-use pesticides were more likely to give birth to a son with cryptorchidism than were a random sample of mothers from the Copenhagen area (6.2% and 1.9%). Furthermore, sons of mothers who directly handled treated plants or were engaged in spraying pesticides had significantly smaller penises than did sons of mothers who had non contact roles in the greenhouse industry (Andersen et al 2008). Last, in a recent meta-analysis of studies from the United States and Europe, Rocheleau et al (2009) reported that maternal occupational exposure to pesticides was associated with a 36% increased risk of hypospadias relative to the risk in mothers without exposure (risk ratio = 1.36; 95% CI, 1.04-1.77).…”
Section: Researchmentioning
confidence: 94%
“…It has been shown that maternal exposure to pesticides during pregnancy is associated with an increased risk of cryptorchidism in male infants (36). A separate study also found that women who worked in greenhouses while pregnant gave birth to sons with significant reproductive health impairment, particularly a three-fold greater risk of cryptorchidism (37).…”
Section: Evidence From Human Retrospective Studiesmentioning
confidence: 97%